Physiochemical properties, antioxidant activity, viability of probiotic bacteria and sensory characteristics of plant-based yogurt fortified with strawberry puree - Mouminah, Haneen Hamed (Journal of Food Technology Research, 2026)
The consumption of plant-based yogurt has increased due to its health benefits and its importance in the nutritional intake of the elderly and individuals with higher energy requirements. Additionally, it provides a lactose-free alternative for people with lactose intolerance and those following a vegetarian lifestyle. This study aimed to enhance the quality characteristics of plant-based yogurt by developing a probiotic and antioxidant-rich product prepared from oat milk supplemented with 8% sugar, 0.5% xanthan gum, and inoculated with 3% ABT-3 starter culture (Streptococcus thermophilus, Lactobacillus acidophilus, and Bifidobacterium bifidum). After fermentation at 39°C for 16 hours, strawberry puree was added at ratios ranging from 0 to 20%. The final products were stored at 4°C for 21 days. The evaluation of the physiochemical characteristics of oat milk and yogurt samples was conducted after preparation, including changes in acidity, pH values, color attributes, phenolic compounds, anthocyanins, antioxidant activities, viable probiotic count, and sensory properties during 21 days of cold storage at 4°C. The results showed that adding strawberry puree to yogurt samples significantly increased total solids, carbohydrates, acidity, phenolic and anthocyanin contents, and antioxidant activity, with these increases being directly proportional to the amount of strawberry puree added. This also improved probiotic viability, maintaining levels above the recommended minimum of 106 CFU/mL or g during cold storage. The yogurt containing 15% strawberry puree achieved the highest sensory scores. The study demonstrates the potential for producing a highly acceptable, antioxidant-rich, probiotic plant-based yogurt from oat milk enriched with strawberry puree.